Theoretical and experimental evaluation of strength indices of bogie frame transoms for trailing cars of electric trains ER9M, ER9E - Bondarev, O. M.; Kryvchykov, O. E.; Yagoda, D. A.; Bondareva, V. S.; Ryadkovskiy, V. V. (Science and Transport Progress, 2013)
Purpose. The article objectives are to identify the factors, which can contribute to the formation of cracks and to develop the measures on improving the strength indices of bogie frame transoms of trailing cars. Methodology. In order to achieve these objectives, in performing the work it was conducted the inspection of the technical condition of supporting structures for bogie frames of trailing cars; measured the Brіnell hardness numbers and estimated the endurance limits of transom material; tested on determination of the levels of efforts and stresses being created in the specified transoms under operation; developed the computational models for the theoretical determination of stress levels in the transom by simulating both normal and abnormal conditions of operating loading. Findings. Based on the analysis of results obtained: the situations with the highest stress levels were found; the measures on improving the strength indices of bogie frame transoms of trailing cars were developed. Originality. Based on the experimental and theoretical studies, the scientific monitoring of works to develop the measures on improving the strength indices of bogie frame transoms of trailing cars was carried out. Practical value. The developed measures on improving the strength indices were passed to professionals of Ukrzaliznytsia to introduce the proposed activities during the repairs of electric trains of specified series.